Prevalence of Achilles Tendinopathy in Female Nurses in Lahore-Pakistan - Sunaina Javed, Muhammad Rehan Amjad, Aqib Mehmood, Hafiz Muhammad Uzair Asghar, Maham Javaid, Ana Avaid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Achilles tendon is the largest & longest tendon in the body. Although Achilles tendinopathy is chiefly a runner’s problem but can affect other populations exposed to a prolonged standing position. Aim: To assess the prevalence of Achilles tendinopathy in nurses due to long standing position and its association with other factors resulting in symptoms. Study design: Cross-sectional study. Methodology: The information was gathered using a standardized VISA-A scale. The study’s sample size was 110 subjects. The VISA A questionnaire had eight items for assessing the condition. Over the course of six months, data was collected from female nurses in Lahore. The data from the questionnaire was organized. Data was analyzed by SPSS software, version 19 as qualitative variables were expressed as mean ± SD. Frequencies and percentages were calculated for individual items. Results: In this study, 39(35.5%) nurses have mild pain, 49(44.5%) nurses have moderate pain & 21(19.1%) nurses have severe pain after walking on flat ground for 30 minutes. The Cross tabulation of Visa- A scale showed that there was a weak or frail relationship between Achilles tendinopathy and prolong standing position. Conclusion: We concluded that there is a weak or frail relationship in Achilles tendinopathy in nurses due to prolong standing position. Most of the population falls in between no pain to mild pain.